A high-strength connecting rod

By using high infrared absorption alkali-resistant glass fiber material and limiting part design, the problem of insufficient strength of the connecting rod in the prior art is solved, and the effect of high strength, durability and easy installation is achieved.

CN119737370APending Publication Date: 2025-04-01JIANGSU XINJIE SCIENCE & EDUCATION EQUIPMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411918458.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The connecting rods used in the prior art rely on the interaction force between different shapes to ensure the strength between the rods, but cannot increase the strength of the individual connecting rods themselves, thereby affecting their safety and life.

Method used

High-infrared alkali-resistant glass fiber material is used to prepare high-strength connecting rods by adding quartz sand, dolomite, graphene and resin to the glass fiber raw materials, and using specific heating and drawing processes. In addition, the first and second limit parts are designed to simplify the installation process and avoid misalignment.

Benefits of technology

It improves the strength of the connecting rod, enhances its impact, bending and tensile resistance, extends service life, and improves installation stability and simplicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119737370A_ABST
    Figure CN119737370A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength connecting rod, comprising a connecting rod, wherein the connecting rod is an alkali-resistant glass fiber rod with high infrared absorption, and the alkali-resistant glass fiber rod with high infrared absorption is prepared from the following raw materials by weight: 20-25 parts of pyrophyllite, 20-25 parts of quartz sand, 30-35 parts of limestone, 5-8 parts of dolomite, 10-13 parts of magnesite, 2-5 parts of nano-graphene and 20-30 parts of resin. The quartz sand has the effects of hardness, wear resistance, high temperature resistance, small thermal expansion coefficient, high insulation and corrosion resistance, the graphene can increase the impact strength of the glass fiber rod by 70%, and the bending elongation by 50%, and the resin makes the glass fiber rod have good toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of connecting rod preparation, in particular to a high-strength connecting rod. Background Art

[0002] Trampoline is a competitive sport in which athletes perform acrobatic skills by rebounding from a trampoline, which requires fence poles and nets to be installed around it for safety protection; For example, the Chinese authorized patent with announcement number CN208003327U (a trampoline guard net pole): includes a trampoline foot tube; a net pole is connected to the trampoline foot tube, and the net pole includes a lower connecting tube and an upper connecting tube; an upper pad and a lower pad are connected between the lower connecting tube and the trampoline foot tube; the lower pad is connected to the lower connecting tube and the trampoline foot tube by a first bolt; the upper pad is connected to the trampoline foot tube by a second bolt and is sleeved with the lower connecting tube through a clamp; the upper connecting tube includes a plug-in straight tube, an arc tube connected to the upper end of the plug-in straight tube, and a connecting straight tube connected to the upper end of the arc tube; the plug-in straight tube is inserted into the upper end of the lower connecting tube and is fixed by a third bolt. In terms of force, the arc tube is less likely to accumulate force in a certain place compared to the existing straight tube, so the force is more uniform and the bending resistance is stronger.

[0003] The connecting rods used in the above-mentioned prior art utilize the interaction force between their different shapes to ensure the strength between the rods, but cannot improve the strength of a single connecting rod itself, thereby affecting its safety and lifespan; therefore, it does not meet the existing needs, and we have proposed a high-strength connecting rod. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength connecting rod to solve the problem that the connecting rods used in the prior art proposed in the above background technology utilize the interaction force between their different shapes to ensure the strength between the rods, but cannot improve the strength of a single connecting rod itself, thereby affecting its safety and lifespan.

[0005] To achieve the above object, the present invention provides the following technical solution: a high-strength connecting rod, comprising a connecting rod, the upper and lower ends of the connecting rod are both provided with connecting holes, a sponge cover is installed on the surface of the connecting rod, an anti-drop round head is provided on the top of the connecting rod, and a fixing rod is installed on the bottom of the connecting rod; and further comprising: A first limiting member, which is arranged at the bottom of the connecting rod, the first limiting member is provided with an inserting hole, and the bottom of the connecting rod is plug-connected with the first limiting member through the inserting hole, and the rear end surface of the first limiting member is provided with a first connecting groove; A second limiting member, which is arranged on the rear end surface of the fixing rod, and two second limiting members are provided, and second connecting grooves are provided on the two second limiting members, and fixing holes are provided in the second connecting grooves; The connecting rod is an alkali-resistant glass fiber rod with high infrared absorption, and the alkali-resistant glass fiber rod with high infrared absorption is prepared by the following preparation method: Step 1: First, crush the raw materials of glass fiber, and then weigh the raw materials for producing glass fiber according to the following weight parts: 20-25 parts of pyrophyllite, 20-25 parts of quartz sand, 30-35 parts of limestone, 5-8 parts of dolomite, 10-13 parts of magnesite, 2-5 parts of nano-graphene and 20-30 parts of resin, mix them evenly and then melt and heat them. The heating process adopts the following method: Step 11: First, increase the temperature from room temperature to 200°C at a rate of 3°C per minute and maintain for 30 minutes; Step 12: Then, the temperature is raised from 200°C to 900°C at a rate of 5°C per minute and maintained for 60 minutes; meanwhile, an inert gas is introduced during the heating process; Step 13: heating the temperature from 900°C to 1000°C at a rate of 3°C per minute and maintaining the temperature for 30 minutes; meanwhile, introducing an inert gas during the heating process; Step 2: Draw the heated raw material into glass fiber, and spray a layer of impregnation agent on the surface of the glass fiber by spraying, so that the high-temperature liquid fiber is quickly cooled to form glass fiber; Step 3: Then, the wetting agent on the surface of the material is removed by calcination, and a SiC transition layer is deposited on the fiber surface as a bonding layer; Step 4: Then, ethylene is used as the source material, and argon is used as the diluent gas and carrier gas for re-deposition, and the material is surface modified with silane coupling agent A1100, and the temperature is lowered at a rate of 12°C per second. After the temperature drops to room temperature, the fiber is taken out, and the fiber is ultrasonically treated for 25 minutes. The material is surface treated with silane coupling agent A187 to attach nano zirconium oxide particles to the surface of the composite material, and the reaction is carried out at 90°C for 3 hours, and then it is immersed in a solvent for 2.5 hours, and finally dried to obtain an alkali-resistant glass fiber with high infrared absorption; Step 5: The prepared glass fiber is then processed, and the fiber glass filaments are placed at a certain oblique angle relative to the core mold axis. The auxiliary angle, i.e., the winding angle, is controlled by the ratio of the moving speed of the dipping tank and the rotation speed of the core mold. The translational movement of the dipping tank is controlled by computerized electromechanical control. The number of winding layers is gradually increased until the designed wall thickness is reached. After the winding is completed, the resin in the product is basically solidified. After curing, the core mold is removed from the FRP tube to obtain the glass fiber rod.

[0006] Preferably, a threaded connection column is provided at the bottom of the anti-slip round head, and a threaded connection column is provided at the top of the fixing rod. The anti-slip round head and the fixing rod are threadedly connected to the connecting holes inside the upper and lower ends of the connecting rod respectively through the threaded connection column.

[0007] Preferably, the transition layer deposited in step 3 uses a mixture of ethylene and silicon tetrachloride as source material, the deposition temperature is 300° C., argon is used as diluent gas and carrier gas, and the deposition time is 20 minutes.

[0008] Preferably, the deposition temperature of the second deposition in step 4 is 300° C., and the deposition time is 1.5 h.

[0009] Preferably, the resin is composed of PP resin, PCE resin, PET resin, PA resin and PC resin, and the weight ratio of the PP resin, PCE resin, PET resin, PA resin and PC resin is 30:15:5:5:8.

[0010] Preferably, the impregnating agent is composed of base silicone oil, triethylenediamine, polymer dispersant and lithium nitrate, and the weight ratio of the base silicone oil, triethylenediamine, polymer dispersant and lithium nitrate is 5:2:3:1.

[0011] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adds quartz sand, dolomite, graphene and resin as raw materials to the glass fiber rod raw materials, wherein quartz sand is a silicate mineral with the functions of hardness, wear resistance, high temperature resistance, small thermal expansion coefficient, high insulation and corrosion resistance. When dolomite is calcined, the magnesium oxide inside it becomes periclase, and the calcium oxide is converted into crystalline a-CaO, with a dense structure, strong water resistance and a refractoriness of up to 2300°C. Graphene is one of the materials with the highest known strength. Graphene can maintain good stability in the range of 4K (about -269°C) deep low temperature to 1273K (about 1000°C) high temperature. Graphene also has good toughness and can be bent. The inherent tensile strength is 130GPa, which can increase the impact strength of the glass fiber rod by 70% and the bending elongation by 50%. The resin is composed of PP resin, PCE resin, PET resin, PA resin and PC resin, which is 2 to 10 times the toughness of conventional resins. Its toughening mechanism can produce plastic deformation, so that the glass fiber rod has good toughness. The connecting rods prepared using the above components solve the defect in the prior art that the strength between the rods needs to be ensured by utilizing the interaction force between different shapes, but the strength of a single connecting rod itself cannot be improved, thereby improving the safety of use and extending the service life.

[0012] 2. The connecting rod prepared by the preparation method of the present invention is an alkali-resistant glass fiber rod with high infrared absorption. The high infrared absorption increases the use of the rod. The good alkali resistance can resist material erosion. At the same time, it has strong grip, extremely high elastic modulus, impact resistance, tensile strength and bending strength, is non-flammable, frost-resistant, and has strong resistance to temperature and humidity changes, and has excellent crack resistance and impermeability. It has the characteristics of strong designability and easy molding.

[0013] 3. The present invention sets a first limiter and a second limiter on the connecting rod. During installation, the first limiter can be used to connect it to the edge of the trampoline to play a positioning role. Then, the second limiter is used to connect the fixed rod on the connecting rod to the bracket of the trampoline to avoid misalignment during installation. The structure is simpler, the stability and strength are better, and the installation and removal are also simpler and faster. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram of the overall structure of the connecting rod and the mounting member of the present invention; In the figure: 1. connecting rod; 2. sponge cover; 3. connecting hole; 4. anti-slip round head; 5. fixing rod; 6. first limiting piece; 7. plug-in hole; 8. first connecting groove; 9. second limiting piece; 10. second connecting groove; 11. fixing hole; 12. threaded connecting column. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0016] See also Figure 1 The present embodiment provides a high-strength connecting rod, including a connecting rod 1, the upper and lower ends of the connecting rod 1 are both provided with connecting holes 3, a sponge cover 2 is installed on the surface of the connecting rod 1, an anti-drop round head 4 is provided on the top of the connecting rod 1, and a fixing rod 5 is installed on the bottom of the connecting rod 1; and further includes: A first stopper 6 is provided at the bottom of the connecting rod 1. A plug hole 7 is provided on the first stopper 6. The bottom of the connecting rod 1 is plug-connected with the first stopper 6 through the plug hole 7. A first connecting groove 8 is provided on the rear end surface of the first stopper 6. The second limiting member 9 is arranged on the rear end surface of the fixing rod 5 , and two second limiting members 9 are provided. The two second limiting members 9 are provided with second connecting grooves 10 , and the second connecting grooves 10 are provided with fixing holes 11 .

[0017] See also Figure 1The bottom of the anti-slip round head 4 is provided with a threaded connection column 12, and the top of the fixed rod 5 is provided with a threaded connection column 12. The anti-slip round head 4 and the fixed rod 5 are respectively threadedly connected with the connection holes 3 inside the upper and lower ends of the connecting rod 1 through the threaded connection column 12. During installation, the first limiter 6 can be used to connect it to the edge of the trampoline to play a positioning role, and then the second limiter 9 is used to connect the fixed rod 5 on the connecting rod 1 to the bracket of the trampoline to avoid misalignment during installation. The first limiter 6 can be set at the notch of the first connecting groove 8 according to actual conditions. In this embodiment, the connecting rod 1 is an alkali-resistant glass fiber rod with high infrared absorption, and the alkali-resistant glass fiber rod with high infrared absorption is prepared by the following preparation method: Step 1: First, crush the raw materials of glass fiber, and then weigh the raw materials for producing glass fiber according to the following weight parts: 20 parts of pyrophyllite, 20 parts of quartz sand, 35 parts of limestone, 5 parts of dolomite, 10 parts of magnesite, 2 parts of nano-graphene and 20 parts of resin, mix them evenly and then melt and heat them. The heating process adopts the following method: Step 11: First, the temperature is raised from room temperature to 200°C at a rate of 3°C per minute and maintained for 30 minutes. This step is to preheat and melt the raw materials; Step 12: Then, the temperature is raised from 200°C to 900°C at a heating rate of 5°C per minute and maintained for 60 minutes; at the same time, an inert gas is introduced during the heating process; this step allows the nano-graphene to fully react with other raw materials, thereby modifying the glass fiber and reducing the probability of bubbles in the glass fiber; Step 13: The temperature is raised from 900°C to 1000°C at a rate of 3°C per minute and maintained for 30 minutes; at the same time, an inert gas is introduced during the heating process; this step is used to remove the gas in the glass fiber, thereby forming a dense glass fiber; Step 2: Draw the heated raw material into glass fiber, and spray a layer of impregnation agent on the surface of the glass fiber by spraying, so that the high-temperature liquid fiber is quickly cooled to form glass fiber; Step 3: Then, the wetting agent on the surface of the material is removed by calcination, and a SiC transition layer is deposited on the fiber surface as a bonding layer; the deposited transition layer uses a mixture of ethylene and silicon tetrachloride as source material, the deposition temperature is 300°C, argon is used as diluent gas and carrier gas, and the deposition time is 20 minutes; Step 4: Then, ethylene is used as the source material, and argon is used as the diluent gas and the carrier gas for re-deposition, the deposition temperature of the deposition is 300°C, and the deposition time is 1.5 hours; then, the material is surface modified with silane coupling agent A1100, and the temperature is lowered at a rate of 12°C per second. After the fiber is cooled to room temperature, the fiber is taken out, and the fiber is ultrasonically treated for 25 minutes. Then, the material is surface treated with silane coupling agent A187 to make nano zirconium oxide particles adhere to the surface of the composite material, and react at 90°C for 3 hours, and then it is immersed in a solvent for 2.5 hours, and finally dried to obtain an alkali-resistant glass fiber with high infrared absorption; Step 5: The prepared glass fiber is then processed, and the fiber glass filaments are placed at a certain oblique angle relative to the core mold axis. The auxiliary angle, i.e., the winding angle, is controlled by the ratio of the moving speed of the dipping tank and the rotation speed of the core mold. The translational movement of the dipping tank is controlled by computerized electromechanical control. The number of winding layers is gradually increased until the designed wall thickness is reached. After the winding is completed, the resin in the product is basically solidified. After curing, the core mold is removed from the FRP tube to obtain the glass fiber rod.

[0018] The resin is composed of PP resin, PCE resin, PET resin, PA resin and PC resin, and the weight ratio of PP resin, PCE resin, PET resin, PA resin and PC resin is 30:15:5:5:8. The resin in this embodiment is 2 to 10 times tougher than conventional resins, and its toughening mechanism can produce plastic deformation, so that the glass fiber rod has good toughness.

[0019] The impregnating agent is composed of base silicone oil, triethylenediamine, polymer dispersant and lithium nitrate, wherein the weight ratio of the base silicone oil, triethylenediamine, polymer dispersant and lithium nitrate is 5:2:3:1.

[0020] Among them, quartz sand is a silicate mineral that is hard, wear-resistant, high-temperature resistant, has a small thermal expansion coefficient, is highly insulating, and corrosion-resistant. When dolomite is calcined, the magnesium oxide inside it becomes periclase, and the calcium oxide is transformed into crystalline a-CaO, which has a dense structure, strong water resistance, and a refractoriness of up to 2300°C. Graphene is one of the strongest materials known. Graphene can maintain good stability in the range of 4K (about -269°C) deep low temperature to 1273K (about 1000°C). Graphene also has good toughness and can be bent. The inherent tensile strength is 130GPa, which can increase the impact strength of glass fiber rods by 70% and the bending elongation by 50%.

[0021] In some embodiments, the alkali-resistant glass fiber rod with high infrared absorption is prepared by the following preparation method: Step 1: First, crush the raw materials of glass fiber, and then weigh the raw materials for producing glass fiber according to the following weight parts: 25 parts of pyrophyllite, 25 parts of quartz sand, 38 parts of limestone, 8 parts of dolomite, 13 parts of magnesia borax, 5 parts of nano-graphene and 30 parts of resin, mix them evenly and then melt and heat them. The heating process adopts the following method: Step 11: First, increase the temperature from room temperature to 200°C at a rate of 3°C per minute and maintain for 30 minutes; Step 12: Then, the temperature is raised from 200°C to 900°C at a rate of 5°C per minute and maintained for 60 minutes; meanwhile, an inert gas is introduced during the heating process; Step 13: heating the temperature from 900°C to 1000°C at a rate of 3°C per minute and maintaining the temperature for 30 minutes; meanwhile, introducing an inert gas during the heating process; Step 2: Draw the heated raw material into glass fiber, and spray a layer of impregnation agent on the surface of the glass fiber by spraying, so that the high-temperature liquid fiber is quickly cooled to form glass fiber; Step 3: Then, the wetting agent on the surface of the material is removed by calcination, and a SiC transition layer is deposited on the fiber surface as a bonding layer; the deposited transition layer uses a mixture of ethylene and silicon tetrachloride as source material, the deposition temperature is 300°C, argon is used as diluent gas and carrier gas, and the deposition time is 20 minutes; Step 4: Then, ethylene is used as the source material, and argon is used as the diluent gas and the carrier gas for re-deposition, the deposition temperature of the deposition is 300°C, and the deposition time is 1.5 hours; then, the material is surface modified with silane coupling agent A1100, and the temperature is lowered at a rate of 12°C per second. After the fiber is cooled to room temperature, the fiber is taken out, and the fiber is ultrasonically treated for 25 minutes. Then, the material is surface treated with silane coupling agent A187 to make nano zirconium oxide particles adhere to the surface of the composite material, and react at 90°C for 3 hours, and then it is immersed in a solvent for 2.5 hours, and finally dried to obtain an alkali-resistant glass fiber with high infrared absorption; Step 5: The prepared glass fiber is then processed, and the fiber glass filaments are placed at a certain oblique angle relative to the core mold axis. The auxiliary angle, i.e., the winding angle, is controlled by the ratio of the moving speed of the dipping tank and the rotation speed of the core mold. The translational movement of the dipping tank is controlled by computerized electromechanical control. The number of winding layers is gradually increased until the designed wall thickness is reached. After the winding is completed, the resin in the product is basically solidified. After curing, the core mold is removed from the FRP tube to obtain the glass fiber rod.

[0022] In some embodiments, the alkali-resistant glass fiber rod with high infrared absorption is prepared by the following preparation method: Step 1: First, crush the raw materials of glass fiber, and then weigh the raw materials for producing glass fiber according to the following weight parts: 23 parts of pyrophyllite, 22 parts of quartz sand, 36 parts of limestone, 6 parts of dolomite, 12 parts of magnesite, 4 parts of nano-graphene and 26 parts of resin, mix them evenly and then melt and heat them. The heating process adopts the following method: Step 11: First, increase the temperature from room temperature to 200°C at a rate of 3°C per minute and maintain for 30 minutes; Step 12: Then, the temperature is raised from 200°C to 900°C at a rate of 5°C per minute and maintained for 60 minutes; meanwhile, an inert gas is introduced during the heating process; Step 13: heating the temperature from 900°C to 1000°C at a rate of 3°C per minute and maintaining the temperature for 30 minutes; meanwhile, introducing an inert gas during the heating process; Step 2: Draw the heated raw material into glass fiber, and spray a layer of impregnation agent on the surface of the glass fiber by spraying, so that the high-temperature liquid fiber is quickly cooled to form glass fiber; Step 3: Then, the wetting agent on the surface of the material is removed by calcination, and a SiC transition layer is deposited on the fiber surface as a bonding layer; the deposited transition layer uses a mixture of ethylene and silicon tetrachloride as source material, the deposition temperature is 300°C, argon is used as diluent gas and carrier gas, and the deposition time is 20 minutes; Step 4: Then, ethylene is used as the source material, and argon is used as the diluent gas and the carrier gas for re-deposition, the deposition temperature of the deposition is 300°C, and the deposition time is 1.5 hours; then, the material is surface modified with silane coupling agent A1100, and the temperature is lowered at a rate of 12°C per second. After the fiber is cooled to room temperature, the fiber is taken out, and the fiber is ultrasonically treated for 25 minutes. Then, the material is surface treated with silane coupling agent A187 to make nano zirconium oxide particles adhere to the surface of the composite material, and react at 90°C for 3 hours, and then it is immersed in a solvent for 2.5 hours, and finally dried to obtain an alkali-resistant glass fiber with high infrared absorption; Step 5: The prepared glass fiber is then processed, and the fiber glass filaments are placed at a certain oblique angle relative to the core mold axis. The auxiliary angle, i.e., the winding angle, is controlled by the ratio of the moving speed of the dipping tank and the rotation speed of the core mold. The translational movement of the dipping tank is controlled by computerized electromechanical control. The number of winding layers is gradually increased until the designed wall thickness is reached. After the winding is completed, the resin in the product is basically solidified. After curing, the core mold is removed from the FRP tube to obtain the glass fiber rod.

[0023] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high-strength connecting rod, comprising a connecting rod (1), wherein the upper and lower ends of the connecting rod (1) are both provided with connecting holes (3), a sponge cover (2) is installed on the surface of the connecting rod (1), an anti-drop round head (4) is installed on the top of the connecting rod (1), and a fixing rod (5) is installed on the bottom of the connecting rod (1); the characteristics are: Also includes: a first limiting member (6) arranged at the bottom of the connecting rod (1); a plug hole (7) being arranged on the first limiting member (6); and the bottom of the connecting rod (1) is plug-connected to the first limiting member (6) via the plug hole (7); and a first connecting groove (8) being arranged on the rear end surface of the first limiting member (6); A second limiting member (9) is arranged on the rear end surface of the fixing rod (5), and two second limiting members (9) are provided, and second connecting grooves (10) are provided on the two second limiting members (9), and fixing holes (11) are provided in the second connecting grooves (10); The connecting rod (1) is an alkali-resistant glass fiber rod with high infrared absorption, and the alkali-resistant glass fiber rod with high infrared absorption is prepared by the following preparation method: Step 1: First, crush the raw materials of glass fiber, and then weigh the raw materials for producing glass fiber according to the following weight parts: 20-25 parts of pyrophyllite, 20-25 parts of quartz sand, 30-35 parts of limestone, 5-8 parts of dolomite, 10-13 parts of magnesite, 2-5 parts of nano-graphene and 20-30 parts of resin, mix them evenly and then melt and heat them. The heating process adopts the following method: Step 11: First, increase the temperature from room temperature to 200°C at a rate of 3°C per minute and maintain for 30 minutes; Step 12: Then, the temperature is raised from 200°C to 900°C at a rate of 5°C per minute and maintained for 60 minutes; meanwhile, an inert gas is introduced during the heating process; Step 13: heating the temperature from 900°C to 1000°C at a rate of 3°C per minute and maintaining the temperature for 30 minutes; meanwhile, introducing an inert gas during the heating process; Step 2: Draw the heated raw material into glass fiber, and spray a layer of impregnation agent on the surface of the glass fiber by spraying, so that the high-temperature liquid fiber is quickly cooled to form glass fiber; Step 3: Then, the wetting agent on the surface of the material is removed by calcination, and a SiC transition layer is deposited on the fiber surface as a bonding layer; Step 4: Then, ethylene is used as the source material, and argon is used as the diluent gas and carrier gas for re-deposition, and the material is surface modified with silane coupling agent A1100, and the temperature is lowered at a rate of 12°C per second. After the temperature drops to room temperature, the fiber is taken out, and the fiber is ultrasonically treated for 25 minutes. The material is surface treated with silane coupling agent A187 to attach nano zirconium oxide particles to the surface of the composite material, and the reaction is carried out at 90°C for 3 hours, and then it is immersed in a solvent for 2.5 hours, and finally dried to obtain an alkali-resistant glass fiber with high infrared absorption; Step 5: The prepared glass fiber is then processed, and the fiber glass filaments are placed at a certain oblique angle relative to the core mold axis. The auxiliary angle, i.e., the winding angle, is controlled by the ratio of the moving speed of the dipping tank and the rotation speed of the core mold. The translational movement of the dipping tank is controlled by computerized electromechanical control. The number of winding layers is gradually increased until the designed wall thickness is reached. After the winding is completed, the resin in the product is basically solidified. After curing, the core mold is removed from the FRP tube to obtain the glass fiber rod.

2. A high-strength connecting rod according to claim 1, characterized in that: A threaded connection column (12) is provided at the bottom of the anti-slip round head (4), and a threaded connection column (12) is provided at the top of the fixing rod (5). The anti-slip round head (4) and the fixing rod (5) are respectively threadedly connected to the connection holes (3) inside the upper and lower ends of the connecting rod (1) through the threaded connection column (12).

3. A high-strength connecting rod according to claim 1, characterized in that: The transition layer deposited in step 3 uses a mixture of ethylene and silicon tetrachloride as source material, the deposition temperature is 300° C., argon is used as diluent gas and carrier gas, and the deposition time is 20 minutes.

4. The high-strength connecting rod according to claim 1, characterized in that: The deposition temperature of the second deposition in step 4 is 300° C., and the deposition time is 1.5 h.

5. The high-strength connecting rod according to claim 1, characterized in that: The resin is composed of PP resin, PCE resin, PET resin, PA resin and PC resin, and the weight ratio of the PP resin, PCE resin, PET resin, PA resin and PC resin is 30:15:5:5:

8.

6. The high-strength connecting rod according to claim 1, characterized in that: The impregnating agent is composed of base silicone oil, triethylenediamine, polymer dispersant and lithium nitrate, and the weight ratio of the base silicone oil, triethylenediamine, polymer dispersant and lithium nitrate is 5:2:3:1.

Citation Information

Patent Citations

  • Trampoline net protecting bar

    CN208003327U